2017
DOI: 10.1016/j.yebeh.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

The experience of living with adult-onset epilepsy

Abstract: The incidence and prevalence of adults diagnosed with epilepsy is higher compared to those diagnosed in childhood, yet the experience of living with adult-onset epilepsy has rarely been examined. Hence, the current study took a phenomenological approach to examining the experience of living with epilepsy following diagnosis in adulthood. Semi-structured interviews were conducted with 39 people from across the UK, diagnosed with epilepsy between the ages of eighteen and sixty, at two points in time, six months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Furthermore, a series of positive actions, such as adapting health behaviours and readjusting life and work goals, were evident, as well as more avoidant strategies of viewing the seizure as an isolated event. Kılınç et al's (2017) study of the experiences of people living with AOE found similar themes. The first theme identified was the unpredictability of seizures where concern about a potential seizure was present even in people who had been seizure-free for years.…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, a series of positive actions, such as adapting health behaviours and readjusting life and work goals, were evident, as well as more avoidant strategies of viewing the seizure as an isolated event. Kılınç et al's (2017) study of the experiences of people living with AOE found similar themes. The first theme identified was the unpredictability of seizures where concern about a potential seizure was present even in people who had been seizure-free for years.…”
Section: Introductionmentioning
confidence: 76%
“…A smaller number of people experience epilepsy for the first time in adulthood. When individuals first experience seizures at age 18 or older, this is classified as adult-onset epileptic seizure (AOES) activity (Bromfield, Cavazos, & Sirven, 2006;Crepeau & Sirven, 2017;Kilinç, van Wersch, Campbell, & Guy, 2017;Ramanathan et al, 2014). When AOES first appear in adulthood, the cause can be the result of damage that happened in the first few years of life due to an infectious disease (Leung, Hon, & Leung, 2018; National Institute of Neurological Disorders and Stroke [NINDS], 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the literature on refractory epilepsy is limited. We know little of patients' perspectives in terms of their views of treatment and care options over the longer term as assessments progress, with studies concentrating on quantitative assessment to examine incidents of treatment and psychosocial impact of the disease [28,29]. Furthermore, few studies have captured the fluidity of changing perceptions and decisions during assessment and over time.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, few studies have captured the fluidity of changing perceptions and decisions during assessment and over time. In order to better understand these aspects, and the build-up to surgery, as a progressive and highly contextualized process, and to adequately clarify the meaning and significance of resective surgery for patients, a qualitative approach was necessary [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation